Prognosis of endometrial cancer patients with and without symptoms at recurrence. Issue 12 (16th August 2016) - Yoshiba, Takahiro; Takei, Yuji; Machida, Shizuo; Taneichi, Akiyo; Sato, Naoto; Takahashi, Suzuyo; Takahashi, Yoshifumi; Saga, Yasushi; Matsubara, Shigeki; Fujiwara, Hiroyuki
Abstract: Aim: During routine follow‐up for postoperative endometrial cancer, we have encountered patients with and without symptoms at recurrence. In this study, we investigated whether or not there is a difference in the prognosis between patients with and without symptoms at recurrence. Methods: We reviewed endometrial cancer patients who had been treated in our hospital between 1998 and 2007. Routine follow‐up was conducted by our facility criteria. We investigated recurrence‐free survival (RFS), presence or absence of symptoms at recurrence, overall survival from recurrence (OSFR), and overall survival (OS). Results: The subjects were 293 patients. Recurrence was detected in 46 patients. The median RFS was 15 (1–103) months. At the time of recurrence, symptoms were present in 14 patients and absent in 32 patients. In groups with and without symptoms at recurrence, the median OSFR were 36 (2–100) and 45 (2–139) months, respectively. The median OS were 55 (6–163) and 100 (11–178) months, respectively. There were no significant differences in either parameter. Independent prognostic factors for OSFR and OS were histopathologic types other than endometrioid carcinoma (vs endometrioid carcinoma, hazard ratio = 3.102 and 3.008, respectively) and RFS of 14 months or shorter (vs 15 months or longer, hazard ratio = 2.378 and 3.739, respectively). Conclusion: There was no difference in the prognosis between the groups with and without symptoms at recurrence. Independent prognostic factors of recurrent patients were histopathologic types and RFS. A large‐scale study should be conducted to examine the necessity of routine follow‐up for detecting recurrence in the absence of symptoms.